BERAGAMA BAHAGIA UNTUK BINA DAMAI: KAJIAN ATAS TEORI KEMATANGAN BERAGAMA WILLIAM JAMES - Ismail, Roni (Living Islam: Journal of Islamic Discourses, 2024)
In the ideal or normative terms, all religions teach the tenet of peace, so that they express a "friendly" face. However, in historical reality, religion often displays an "angry" face and is used as a tool for hostility, hatred, violent conflict, and even war. Cassanova calls this the Janus face or double face of religion. Religious scholars, practitioners and academics have made various efforts to return religion to its ideal face as a power of peace, brotherhood, unity and humanity. Some propose a peaceful, inclusive, pluralist, dialogical, archipelagic, progressive religiosity, and so on. This article offers a happy religion or religiosity through a psychology of religion approach as participation in discussions of religion for peace, through a study of William James' mature religious theory. James' four mature religious criteria are: (1) always feeling God's presence in life, (2) His presence gives rise to surrender to God and His values, (3) self-surrender gives rise to happiness, freedom and loss of ego, and , (4) changing emotions into love and harmony, are indicators of religious happiness. Happy religiousity are unlikely to hurt, hate, get involved in hostility and violent conflict in the name of religion, but are instead able to spread happiness and peace to others. Happy religiosity are able to build peace, namely: maintaining the sacredness of life and upholding the ideal of life's happiness. Keywords: Happy Religiosity, Mature Religion William James, Peace. Secara idealitas-normatif, semua agama memuat ajaran damai sehingga berwajah “ramah”. Akan tetapi, secara realitas-historis seringkali agama menampilkan wajah “marah” dijadikan alat permusuhan, kebencian, konflik kekerasan, bahkan perang. Cassanova menyebut ini sebagai janus face atau wajah ganda agama. Para agamawan, praktisi dan akademiki telah melakukan berbagai upaya untuk mengembalikan agama pada idealitasnya sebagai pejuang kedamain, persaudaraan, persatuan, dan kemanusiaan. Ada yang menggagas beragama damai, inklusif, pluralis, dialogis, nusantara, berkemajuan, dan lain-lain. Artikel ini menawarkan beragama bahagia melalui pendekatan psikologi agama sebagai keikutsertaan dalam diskusi fungsi beragama untuk perdamaian, melalui kajian atas teori beragama matang dari William James. Empat kriteria beragama matang James, yaitu: (1) merasakan selalu kehadiran Tuhan dalam hidup, (2) kehadiran-Nya memunculkan kepasrahan kepada Tuhan dan nilai-nilai-Nya, (3) kepasrahan diri memunculkan kebahagiaan, kebebasan, dan hilang ego, dan, (4) mengubah emosi menjadi cinta dan harmoni, merupakan indikator kebahagiaan keagamaan. Orang beragama bahagia tidak mungkin menyakiti, membenci, terlibat permusuhan dan konflik kekerasan atas nama agama, tetapi justru mampu menebar kebahagiaan dan perdamaian kepada sesama. Orang beragama bahagia mampu membangun perdamaian, yaitu: menjaga sakralitas kehidupan dan menjunjung ideal kebahagiaan hidup. Kata Kunci: Beragama Bahagia, Beragama Matang William James, Perdamaian.